Memories of the Future: Traditional Russian Administrative Practices in New Foreign Policy Conditions. Article Four. Between Empire and Federation. End of the XIX — beginning of the XX century - N. M. Mezhevich; V. A. Shamakhov (Управленческое консультирование)
The territorial-political structure of the Russian Empire has been studied quite well. The challenge is adapting historical knowledge to current management practices. Russia was not an empire, but it was also not a classical federation. Approximately 35 % of the country was governed in special regimes. This design can be criticized, but this management model did not catalyze the disaster of the beginning of the 20th century. The causes of the crisis were related to public administration issues. In turn, the study of the territorial-political structure will reveal not only the weak, but also the strengths of the management model of imperial Russia.